Translation And Arabicization Strategies Of English Scientific And Technical Terms Into Arabic And Their Dissemination In The Arab Press - Al-Douri, Ghada Saeed Salman (2018)
Arabic Language Academies (ALAs) have made every possible effort to introduce terminologies in Arabicized forms into the Arabic language. However, the academy‟s Arabicized terms have not been well distributed in the language-related sectors, including the media. This study aims to investigate strategies of coining Arabicized scientific and technical terms, as well as the extent of implementation of these terms in the Arab press to support the academy‟s efforts. The linguistic and extralinguistic factors, which affect the dissemination of the ALA‟s Arabicized terminology in the Arab press, are also investigated.